Comparison between small radiation therapy electron beams collimated by Cerrobend and tubular applicators. (8th January 2015) - Di Venanzio, Cristina; Marinelli, Marco; Tonnetti, Alessia; Verona‐Rinati, Gianluca; Bagalà, Paolo; Falco, Maria Daniela; Guerra, Antonio Stefano; Pimpinella, Maria
Abstract : The purpose of this study was to compare the dosimetric properties of small field electron beams shaped by circular Cerrobend blocks and stainless steel tubular applicators. Percentage depth dose curves, beam profiles, and output factors of small‐size circular fields from 2 to 5 cm diameter, obtained either by tubular applicators and Cerrobend blocks, were measured for 6, 10, and 15 MeV electron beam energies. All measurements were performed using a PTW microDiamond 60019 premarket prototype. An overall similar behavior between the two collimating systems can be observed in terms of PDD and beam profiles. However, Cerrobend collimators produce a higher bremsstrahlung background under irradiation with high‐energy electrons. In such irradiation condition, larger output factors are observed for tubular applicators. Similar dosimetric properties are observed using circular Cerrobend blocks and stainless steel tubular applicators at lower beam energies. However, Cerrobend collimators allow the delivery of specific beam shapes, conformed to the target area. On the other hand, in high‐energy irradiation conditions, tubular applicators produce a lower bremsstrahlung contribution, leading to lower doses outside the target volume. In addition, the higher output factors observed at high energies for tubular applicators lead to reduced treatment times. PACS number: 87.53.Bn, 87.55.Qr, 87.56.Fc